Impact of Quercus infectoria Galls Extract on Thyroid Gland and Testicular Functions in Diabetic Rats - Ibrahim, Salam H (The Iraqi Journal of Veterinary Medicine, 2021)
Diabetes mellitus has been reported to be accompanied by thyroid and testicular dysfunctions. The objective of this study was to investigate the effect of Quercus infectoria galls (QIg) extract on the thyroid gland and testicular functions in diabetic rats. Sixteen rats were randomly divided into four equal groups, consisting of normal control, diabetic untreated control, diabetic treated with oral administration of 500 mg/kg BW and 1000 mg/kg BW, respectively for 15 days. Serum blood glucose, thyroid stimulating hormone (TSH), triiodothyronine (T3), thyroxine (T4), testosterone (T), and luteinizing hormone (LH) were assessed. At the end of the experimental period, the rats were euthanized for histopathological analysis of thyroid gland and testis. Furthermore, immunohistochemistry was used to assess the expression of thyroid transcription factor-1 (TTF-1) in the thyroid gland of rats. The significant increase in serum blood glucose level in diabetic rats (DC) was markedly decreased by treatment with QIg extract (500 mg and 100 mg/kg BW) almost to the normal level. The reduced thyroid hormones, both the T3 and T4 were significantly recovered after 15 days of treatment with QIg extract (500 mg and 100 mg/kg BW). Whereas serum concentration of testosterone was significantly reduced in diabetic rats with QIg extract (500 mg and 100 mg/kg BW) treatment. Histopathological analysis of diabetic rats showed a wide range of morphological alterations in thyroid gland and testicular structures, which were almost completely, restored back to normal by treatment of rats with QIg extract. Furthermore, results showed overexpression of TTF-1 in the thyroid gland of diabetic rats, which was recovered back to normal expression after 15 days of treatment with QIg extract. These findings may provide new insights into the potential role of QIg extract as a promising therapeutic agent against diabetic complications in thyroid gland and testicular functions.